Development of a Time-Cost Model for Construction Projects in Rivers State University, Nigeria - Kenneth Miebaka Oba; Kelechukwu Dimkpa (International Journal of Engineering and Management Research, 2024)
This study aimed to develop a mathematical model to address the problems of construction costs and delays in buildings owned by tertiary institutions in Nigeria. A total of eleven building construction projects awarded and executed at Rivers State University between 2016 and 2023 were studied. Bromilow’s Time-Cost (BTC) model, a non-linear power regression mathematical model was developed. The study showed that 1916.3 working days are required to complete a building construction in the Rivers State University, Nigerian, for every Aus1 million. The model predictions resulted in R2 value of 0.7465 which was subjected to two-tailed student t-tests for the for the construction times and costs. The statistical results indicate that the model is fit and adequate. The study also proved that the BTC model is applicable in Nigerian tertiary institutions, especially Rivers State University.